Polymer based optical waveguides - Shee, Yu Gang (2005)
Optical waveguides are structures that confine and direct optical signals in a region of higher effective index than its surrounding media. For integrated optics and photonic applications, it is often of importance to prepare waveguides in the form of thin film structures. Polymeric materials are particularly attractive in integrated optics because of their ability to be processed rapidly, cost-effectively, and with high yields. Polymeric materials are allowed to form compact optical circuits by offering large refractive index contrasts. A new polymeric material: CYCLOTENEâ„¢ PhotoBCB 4024-40 from DOWÂ® Chemical had been adopted in this study for the development of optical waveguides. The behavior of light propagation and the confinement of light in a polymer based optical waveguide had been investigated. The characteristics of the waveguide had been simulated by finite difference method in MATLAB programming environment to obtain the optimum structure for waveguide fabrication. Planar slab waveguides and single mode straight waveguides have been fabricated using low cost photolithographic techniques and wet chemical etching processes. The properties of the polymer material and the fabricated waveguides have been characterized. The experimental results have demonstrated optical waveguiding in the polymer material. Attenuation of single mode optical waveguides at 633 nm and 1550nm with waveguide losses of 1.62 dB/cm and 3.6304 dB/cm have been obtained respectively. Even though the losses are rather high, the polymer material is still suitable as a waveguiding material in the optical interconnect situations by optimizing the fabrication process.